Caught-off guard: Unguarded mitral valve orifice in usual atrial arrangement with discordant atrioventricular connections and pulmonary atresia - Nayan Banerji; Mani Ram Krishna; Raman Krishna Kumar; Robert H Anderson (Wolters Kluwer Medknow Publications, 2020)
Unguarding of an atrioventricular valvar orifice is a rare form of congenital heart disease that requires staged functionally univentricular palliation. Unguarding of the mitral valvar orifice has previously been reported in the setting of mirror-imaged atrial arrangement. We report a neonate with unguarding of the mitral valvar orifice in the setting of usual atrial arrangement, but with discordant atrioventricular connections and pulmonary atresia.